Bojkovice: Transformation of a peripheral micro-region at the Czech-Slovak border - Vaishar, Antonín; Šťastná, Milada (Bulletin of Geography. Socio-economic Series, 2016)
The paper analyses the problem of a rural region in the peripheral position. Bojkovice micro-region on the Czech (Moravian)-Slovak border has been chosen as a case study. Economic transformation of productive and non-productive branches, demographic development (depopulation and aging) and networking in the area were characterized by using statistical data and field research. Development, understood as improvement in quality of life and not in sense of quantitative growth, is highlighted with regard to the changing perception of the countryside. The question remains: how to use peripherality for prosperity? Peripheral countryside is known as "the right countryside" in comparison to suburbanized and globalized countryside in core regions. Based on the research, production embedded in local sources and traditions, ecological agriculture using the protection of landscape and soft tourism are proposed as solutions. Networking like the association of municipalities, LEADER local action group or White Carpathian Euroregion could be the instruments of micro-regional collaboration. The human and social factors seem to be more important than objective conditions. Long-term population stability is the main advantage. However, a lower level of formal education could be a problem. The character of social capital is considered as a decisive circumstance - whether it is passive social capital resistant to outer innovations or active social capital open for now ideas.